Obligate role for Rock1 and Rock2 in adult stem cell viability and function. Issue 3 (March 2023) - Sambandam, Arivazhagan; Storm, Elaine; Tauc, Helen; Hackney, Jason A.; Garfield, David; Caplazi, Patrick; Liu, John; Zhang, Juan; Zhang, Hua; Duggan, Jeff; Jeet, Surinder; Gierke, Sarah; et al.
Abstract: The ability of stem cells to rapidly proliferate and differentiate is integral to the steady-state maintenance of tissues with high turnover such as the blood and intestine. Mutations that alter these processes can cause primary immunodeficiencies, malignancies and defects in barrier function. The Rho-kinases, Rock1 and Rock2, regulate cell shape and cytoskeletal rearrangement, activities essential to mitosis. Here, we use inducible gene targeting to ablate Rock1 and Rock2 in adult mice, and identify an obligate requirement for these enzymes in the preservation of the hematopoietic and gastrointestinal systems. Hematopoietic cell progenitors devoid of Rho-kinases display cell cycle arrest, blocking the differentiation to mature blood lineages. Similarly, these mice exhibit impaired epithelial cell renewal in the small intestine, which is ultimately fatal. Our data reveal a novel role for these kinases in the proliferation and viability of stem cells and their progenitors, which is vital to maintaining the steady-state integrity of these organ systems.